2020
DOI: 10.31969/pusaka.v8i2.423
|View full text |Cite
|
Sign up to set email alerts
|

Kearifan Lokal Sintuwu Maroso sebagai Simbol Moderasi Beragama

Abstract: Moderasi beragama akan menjaga kemajemukan dalam masyarakat dan tidak mengandug paham tertentu, modal sosial merupakan nilai yang dimiliki oleh individu maupun kelompok yang dapat menjadikan mereka saling menghargai. Pluralisme sebagai elemen pengikat dan pemersatu bangsa, sedangkan perpecahan akan menimbulkan sikap ekstrem yang bisa memusuhi dan tidak memiliki faktor pemersatu. Kesadaran ini harus dibangun dengan sikap yang mengharuskan setiap individu atau kelempok dengan mengedepankan keseimbangan. Peneliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…74 It can also be done through various activities that contain local culture and Islamic cultural traditions, especially in student organizations where they have regular activities like discussions on religious integration, local culture and Islamic culture. 75 Millennials can participate in developing local traditions and wisdom as well as maintain previous cultural values and open to contemporary and global culture. It is, therefore, the accommodation of tradition or culture does not mean rejecting global culture, but rather preserving the local values of wisdom as part of nation dignity.…”
Section: Accommodating Local Culturementioning
confidence: 99%
“…74 It can also be done through various activities that contain local culture and Islamic cultural traditions, especially in student organizations where they have regular activities like discussions on religious integration, local culture and Islamic culture. 75 Millennials can participate in developing local traditions and wisdom as well as maintain previous cultural values and open to contemporary and global culture. It is, therefore, the accommodation of tradition or culture does not mean rejecting global culture, but rather preserving the local values of wisdom as part of nation dignity.…”
Section: Accommodating Local Culturementioning
confidence: 99%
“…Culture has symbols that differentiate one another. The symbol represents group or individual identity (Nur, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, local wisdom of reog ponorogo nuanced religious moderation has not been much explored. Nur (2020) examines religious moderation from the perspective of local wisdom in Sintuwu Maroso. Similarly, Aksa et al (2020) found that the Donggo community in Bima has the culture and local wisdom values that are worth emulating in instilling an attitude of religious moderation among the community.…”
Section: Introductionmentioning
confidence: 99%